2015
DOI: 10.1123/ssj.2013-0083
|View full text |Cite
|
Sign up to set email alerts
|

Touchy Subject: A Foucauldian Analysis of Coaches’ Perceptions of Adult-Child Touch in Youth Swimming

Abstract: It has been suggested that child safety discourses are creating an environment in which safety from abuse defines every act of adult-child touch as suspicious, resulting in adults who work with children being positioned as 'risky' and child-related settings becoming no-touch zones. Research on the impact of these discourses on coaches is limited and there have been few attempts to theorize coaches' behaviours to better understand how child safety concerns impact on their practice. Focusing on coaches' avoidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…One of the key findings from the study was that coaches considered it good practice to educate youth athletes about what they referred to as 'good' or 'optimal' nutrition and consequently, particularly among coaches at the elite end of the performance spectrum, they enforced strict dietary rules, in some cases attempting to control athletes' lifestyles way beyond the swimming pool to achieve this. Other key findings from the study have been reported elsewhere (see Lang, 2010Lang, , 2014Lang and Light, 2010), but only data relating to coaches' views on discourses of nutrition and that has not previously been published is used here.…”
Section: The Studymentioning
confidence: 99%
“…One of the key findings from the study was that coaches considered it good practice to educate youth athletes about what they referred to as 'good' or 'optimal' nutrition and consequently, particularly among coaches at the elite end of the performance spectrum, they enforced strict dietary rules, in some cases attempting to control athletes' lifestyles way beyond the swimming pool to achieve this. Other key findings from the study have been reported elsewhere (see Lang, 2010Lang, , 2014Lang and Light, 2010), but only data relating to coaches' views on discourses of nutrition and that has not previously been published is used here.…”
Section: The Studymentioning
confidence: 99%
“…In addition, sport as a field of enquiry is often situated outside of mainstream social science. This paper attempts to contribute to a growing body of literature that has begun to address this (see [3,[23][24][25][26][27][28]). In particular, through the perspectives of SLOs, we explore the relationship between individual SLOs and their organization.…”
Section: Social Science and The Study Of Child Protection In Sportmentioning
confidence: 99%
“…In response to such accounts, it is worth noting that the limited research on this topic has tended to describe coaches' actions without theoretical explanation other than to point the finger of blame at 'restrictive' child protection regulations (Lang 2015 is a notable exception; cf. Lang 2015and Piper et al 2012a). In addition, many studies fail to consider that these coaches may be misinterpreting child protection regulationsthere are, for example, no regulations that prohibit appropriate (adult) coach-(child) athlete touch (see CPSU 2015)and/or that coaches' concerns may be prompted by anger or frustration at challenges to their traditional coaching practices, a reluctance to accept that children's welfare is now a legitimate part of their responsibility (see for example, Hartill and Lang 2014), or at what they perceive as 'interference' from outside agencies (see Gleaves and Lang, forthcoming).…”
mentioning
confidence: 99%
“…In sport, for example, research suggests that, in awareness of this new childsafety discourse, some coaches are changing their practice out of concern they could be accused of abuse , Piper 2015, Piper et al 2012a. Lang ( , 2015, for example, found some swimming coaches positioned themselves as 'safe' by ensuring they were perpetually visible and by limiting their use of adult-child physical contact to avoid being accused of sexual or physical abuse. Similar reluctance to touch child athletesand anger and resentment at thishas subsequently been identified among some coaches in other sports, including rugby, gymnastics, football and paddle sports (Piper 2015, Piper et al 2012a.…”
mentioning
confidence: 99%
See 1 more Smart Citation